Quality of life of caregivers of children with cerebral palsy - doi:10.5020/18061230.2008.p275 - Oliveira, Maria de Fátima Santiago de (2012)
Objective: To understand the quality of life of caregivers of children with cerebral palsy. Methods: A qualitative study held at the Nucleus of Treatment and Precocious Stimulation (NUTEP) with eight caregivers of children with moderate to severe cerebral palsy. Data collection was carried out by means of semi-structured interviews. They were recorded and transcribed, afterwards codified, analyzed and interpreted according to the “content analysis”. Results: The main identified categories were: faced difficulties (transport, financial resources, and health), social life (leisure), projects of life and coping strategies (religiosity). Conclusion: The quality of life of the caregivers can be understood as unsatisfactory. Nevertheless, even in face of difficulties, they find coping strategies for the act of caring, like religiosity; being this a pillar to sustain their lives.